Genomic evolution and ecotype divergence in thraustochytrids: insights from comparative genomics and phylogenomics - Wen, Yingying; Zhu, Xingyu; Li, Jiaqian; Liu, Xiuping; Li, Qixuan; Wang, Guangyi (Frontiers in Microbiology, 2025)
BackgroundThraustochytrids are unicellular heterotrophic protists within the Stramenopiles group, widely distributed across marine ecosystems. Understanding the mechanisms underlying their metabolic ecotype evolution is pivotal for revealing how these organisms drive the marine carbon cycle and adapt to diverse environments.MethodsIn this study, we report a high-quality genome of Aurantiochytrium sp. TWZ-97 and conduct a comparative genomics analysis of thraustochytrid strains to investigate ecotype-specific differences in genome structure, evolutionary-developmental relationships, and core functional genes.ResultsComparative genomics revealed that “anabolic” strains (TWZ-97, Mn4, SW8) possess larger genomes with lower gene density, whereas “catabolic” strains (S-28, S-429) have smaller, gene-rich genomes with stable repetitive elements. Phylogenetic analyses revealed that the “anabolic” strains diverged relatively recently, around 2.389 million years ago, while the “catabolic” strains evolved independently for over 190.7 million years, reflecting prolonged, lineage-specific adaptation. Functionally, “anabolic” strains were enriched in fatty acid synthase genes, whereas hydrolytic enzyme genes were unique to the “catabolic” strains. Both ecotypes exhibited a significant abundance of fatty acid desaturase (FAD) genes, and polyketide synthase (PKS) genes displayed unique long sequences, multi-domain architectures, and ecotype-specific gene differentiation patterns.ConclusionTogether, this study provides crucial molecular evidence for the genetic basis of metabolic specialization and ecotype diversification in thraustochytrids.